Functional organization of the primary motor cortex in psychosis and the potential role of intereffector regions in psychomotor slowing - Sebastian Walther; Florian Wüthrich; Anastasia Pavlidou; Niluja Nadesalingam; Stephan Heckers; Melanie G. Nuoffer; Victoria Chapellier; Katharina Stegmayer; Lydia V. Maderthaner; Alexandra Kyrou; Sofie von Känel; Stephanie Lefebvre (Proceedings of the National Academy of Sciences, 2025)
Altered psychomotor behavior in psychosis is poorly understood. Novel insights into the physiology of the motor cortex prompted a revision of the motor homunculus. Next to core motor effector areas, the primary motor cortex (M1) contains intereffector regions with more integrative connectivity patterns, suggestive of serving psychomotor behavior. Here, we test whether patterns of connectivity differ between patients with and without psychomotor slowing and which cortical areas are associated with aberrant motor behavior in psychosis. This resting-state functional MRI study included 83 patients with psychosis and psychomotor slowing, 43 patients without psychomotor slowing, and 63 matched healthy subjects. We tested group differences in connectivity and regressed motor behavior measures with connectivity in patients with psychomotor slowing. Across subjects, we found distinct rs-fMRI connectivity profiles of the intereffector areas in M1, extending to premotor cortices and cerebellum. Patients with psychomotor slowing had stronger connectivity from the intereffectors than controls or patients without slowing. Finally, motor behavior correlated with connectivity from M1 intereffector regions in patients. Connectivity profiles of intereffectors suggest a role in planning and controlling complex behavioral repertoires. Collectively, these findings in patients with psychomotor slowing stress the importance of intereffector regions in shaping psychomotor behaviors in mental disorders.